Desmoplastic fibroblastoma of the left upper arm. (26th January 2018) - Grewal, Reetu; Natter, Patrick; Makary, Raafat; Silliman, Julia
Abstract : An elderly female patient presented to the clinic with a several-week history of a mass in her left upper arm that was tender to the touch. The mass was initially thought to be a schwannoma of the left radial nerve based on imaging and was surgically removed. The pathology report revealed an uncommon diagnosis of desmoplastic fibroblastoma.